Leadership Strategy of School Principals in Manifesting Religious Moderation: The Case of Islamic Vocational Senior High Schools in East Java - Supriyadi, Ahmad; Kurdi, Muqarramah Sulaiman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The role of school principals in encouraging moderate attitudes toward religion amid increasing radicalism among students. This study examines school principals' leadership in implementing religious moderation at two Islamic Vocational Senior High Schools: SMK NU Tulungagung and SMK Islam 1 Durenan Trenggalek. It aims to understand the leadership style of school principals in instilling religious moderation values and the learning process and implementation of these values. This study uses a qualitative descriptive method with managerial, pedagogical, sociological, and psychological approaches. The research data sources include principals, teachers, and students from both schools. Data collection techniques employ participant observation, in-depth interviews, and documentation. Data analysis employs the Miles and Huberman model, which involves data condensation, presentation, and conclusion. The theoretical studies used include leadership theory in education and religious moderation. The results show that these values occur informally and are already part of the school culture, although no written policy specifically regulates them. This process has proven effective in shaping students' moderate attitudes, increasing tolerance, and strengthening the love of the homeland in both schools